Are Good Corporate Governance, Corporate Social Responsibility, Firm Size And Profit Quality Affect Firm Performance? - Dientri, Abdul Manaf; Darmayanti, Novi; Tri Lestari; Imam Baidlowi; Tri Retno Hariyati (Future Science, 2023)
The purpose of this research is to examine the effect of good corporate governance, corporate social responsibility, company size and earnings quality on the performance of companies listed on the Indonesian stock exchange in 2018-2022. This research was conducted at the Investment Gallery of the University of Muhammadiyah Gresik, by examining the annual financial reports of manufacturing companies listed on the Indonesia Stock Exchange. Population 226 companies. This study used a purposive sampling technique in sampling and obtained 9 companies that were selected based on the criteria. Descriptive statistical analysis and multiple linear regression analysis were used to determine the effect of good corporate governance, corporate social responsibility, company size and earnings quality on company performance. in this study also used the classical assumption test, t test and F test, these techniques were processed with SPSS to analyze several hypotheses. The results of this study indicate that good corporate governance partially has a positive and significant effect on company performance. Corporate social responsibility partially does not affect company performance. Firm size partially has a negative effect on firm performance. earnings quality partially does not affect company performance and simultaneously GCG, CSR, company size and earnings quality affect company performance.